Financial Management Behavior: Case Study of Gen Z and Millennial Gen Bekasi Regency - Latif, Abdul; Apriani, Erna; Afandi, Dian Rachmawati; Sabilla, Akfika Rizky (Riwayat: Educational Journal of History and Humanities, 2025)
The role of Gen Z and Gen Millennials is vital as social capital, the financial behavior of Gen Z and Gen Millennials is an important capital in the future journey of the Indonesian economy, and the financial management behavior of Gen Z and Gen Millennials will have an impact on the level of education and finance, from this urgency the financial management behavior of Gen Z and Gen Millennials needs to be studied as an urgency in this study. The research objectives are formulated using specific objectives by analyzing the role of financial knowledge, personality traits, and education level in the financial management behavior of Gen Z and Gen Millennials. The data analysis method in this research is a quantitative approach. The analysis method uses Structural Equation Modeling (SEM) with SmartPLS software. The study samples were Gen Z and Gen Millennials in Bekasi Regency. The research sampling technique used purpose sampling with online and direct questionnaire techniques and interviews. The sample determined by the purpose sampling technique was 100 respondent samples. The results showed that the financial knowledge variable has no effect on financial management behavior, the personality traits variable has a significant effect on financial management behavior, and the level of education variable significantly affects the financial management behavior of Gen Z and Gen millennials in Bekasi Regency.